What's missing on the London agenda of the G20 - Heribert Dieter; Lena Schipper (Stiftung Wissenschaft und Politik (SWP), 2009)
On 2 April, the leaders of the G20 will meet in London to discuss reforms of the inter-national financial architecture and to agree on co-ordinated measures to deal with the global economic crisis. EU countries have already made suggestions concerning the future stabilisation of financial markets. However, a number of important questions appear to have been left off the agenda so far. For instance, it is not clear what kind of sanctions could and should be imposed on countries unwilling to cooperate in such stabilisation measures. In addition, neither the problems deriving from global im-balances nor potential ways of solving them are being discussed at all, which appears surprising considering current developments. It appears that, rhetoric notwithstand-ing, governments are only aiming at a small scale modification of the financial archi-tecture
Keywords: 320